INTERNATIONAL LEGAL ANALYSIS OF THE BOYCOTT PRODUCTS SUSPECTED OF SUPPORTING GENOCIDE - Sutrisno, Andri (IBLAM LAW REVIEW, 2024)
This jurnal explores the significance of boycotting products suspected of supporting genocide within the framework of international law. The complex relationship between human rights, state responsibility to prevent genocide, and the international community's response to violations of international norms is at the heart of this investigation. The study defines boycott as a form of isolation undertaken by individuals or groups against an entity, encompassing actions like blacklisting, embargoes, and blockades, targeting various products from consumer goods to academic and sports products. Governments, either individually or collectively, issue boycott resolutions, as exemplified by Arab countries' historic boycott against Israel. The paper also introduces other forms of boycotts, such as investment withdrawal, divestment, and sanctions, citing examples like Sudan. Framing the discussion within the context of the United Nations Genocide Convention, the jurnal argues that product boycotts can serve as tools for enforcing compliance with the convention, holding states accountable for preventing genocide. Moreover, product boycotts play a vital role in the international public sphere, mobilizing global public opinion and exerting social, economic, and political pressure on perpetrators of genocide. The study addresses critical questions, focusing on the role of product boycotts as sanctions in international law and their impact on garnering global support and pressuring perpetrators, while providing a voice to victims. The research methodology employed is normative legal research, relying on literature review and secondary legal sources, including journals, articles, and news related to the international legal analysis of the boycott of products suspected of supporting genocide. The jurnal concludes by emphasizing the importance of boycotting products suspected of supporting genocide within the international legal framework, not only as a form of protest but as a